Ostrácodos podocopas del Ordovícico de la Precordillera de San Juan, Argentina (Ameghiniana, 2014)
The podocope ostracods from the Early Llanvirn to Early Caradoc rocks of the Precordillera Basin (Las Chacritas and Las Aguaditas Formations) are described. Sixteen species have been recognized. One genus and seven species are new: Kozuriscapha rectangulata sp. nov., Elliptocyprites ? magna sp. nov., Longiscula sudamericana sp. nov., Agustina aguiñe! gen. et sp. nov., Medianella sanchezae sp. nov., Steusloffina ? sterrenae sp. nov. and Pactujdomelloides maequatis sp. nov. Two different associations have been recognized, one in the Early Llanvirn another one in the Early Caradoc. They allow local correlation between the basal part of the Las Aguaditas Formation and the Las Chacritas Formation and between the middle part of the Las Aguaditas Formation and the Mogotes Azules section. Three of the eleven genera described are endemic, and the remaining are pandemic.